Predicting outcome of epilepsy after meningioma resection. Issue 7 (18th December 2015) - Wirsching, Hans-Georg; Morel, Corinne; Gmür, Corinne; Neidert, Marian Christoph; Baumann, Christian Richard; Valavanis, Antonios; Rushing, Elisabeth Jane; Krayenbühl, Niklaus; Weller, Michael
Abstract: Background: Surgical excision is the standard treatment for intracranial meningiomas. Epilepsy is a major cause of morbidity in meningioma patients, but postoperative control of epilepsy is not achieved in a substantial fraction of patients. The purpose of this study was to define risk factors for postoperative epilepsy. Methods: Patients treated for histologically confirmed intracranial meningioma at the University Hospital Zurich between 2000 and 2013 were retrospectively analyzed. Demographic, clinical, imaging, and electroencephalographic data were assessed. A binary regression model was applied to identify risk factors for postoperative epilepsy. Results: Of the 779 patients analyzed, epileptic seizures occurred in 244 (31.3%) patients before surgery and in 204 (26.6%) patients after surgery. Of the 244 patients with preoperative epilepsy, 144 (59.0%) became seizure-free after surgery; of the 535 patients without preoperative seizures, 104 (19.4%) suffered from epilepsy after surgery. Risk factors for postoperative epilepsy were preoperative epilepsy (odds ratio [OR]: 3.46 [95% confidence interval CI: 2.32–5.16]), major surgical complications including CNS infections (OR: 5.89 [95% CI: 1.53–22.61]), hydrocephalus (OR: 3.27 [95% CI: 1.35–7.95]), recraniotomy (OR: 2.91 [95% CI: 1.25–6.78]), and symptomatic intracranial hemorrhage (OR: 2.60 [95% CI: 1.17–5.76]) as well as epileptiform EEG potentials (OR: 2.52 [95% CI: 1.36–4.67]), younger age (OR: 1.74 [(95% CI: 1.18–2.58]), and tumor progression (OR: 1.92 [95% CI: 1.16–3.18]). Postoperative improvement or recovery from preoperative neurologic deficits was associated with improved seizure control (OR: 0.46 [95% CI: 0.25–0.85], P = .013). Conclusion: We suggest prospective validation of a score ("STAMPE2") based on clinical findings, EEG, and brain-imaging measures to estimate postoperative seizure risk and guide anticonvulsant treatment in meningioma patients.